POLICY OF "CULTURAL REVOLUTION" IN UZBEKISTAN AND METHODS OF ITS IMPLEMENTATION - Ergasheva Yulduz Alimovna; Ergasheva Gulnoz Alimovna (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2020)
The article examines the implementation of the Soviet policy of the "cultural revolution" in Uzbekistan, its essence and ideological foundations, as well as the measures of the Soviet government to Sovietize the national culture. The article highlights the positive and negative consequences of the introduction of the Soviet cultural policy on the spiritual and cultural life of the people